Annual Plan Programme 2001-2002 Volume-IV Andaman and Nicobar Administration - Planning Commission (Planning Commission, 2001)
Early Childhood Care and Education is meant to promote assured access to every child for the fulfillment of all basic needs through the period of his growth and to prepare for his formal schooling. ECCE is expected to provide for a holistic development of the child i.e. social educational, health, physical, nutritional and psychological needs. The National Programme of Education emphasis the need for starting ECCE Centres on priority for the groups who are still outside the mainstream of formal education and envisages that the entire population in the age group 3-6 years should be provided comprehensive ECCE by 2000 A.D.
Andaman and Nicobar Administration, Planning Department